Down-regulation of miR-144 elicits proinflammatory cytokine production by targeting toll-like receptor 2 in nonalcoholic steatohepatitis of high-fat-diet-induced metabolic syndrome E3 rats. (15th February 2015) - Li, Dongmin; Wang, Xuan; Lan, Xi; Li, Yue; Liu, Li; Yi, Jing; Li, Jing; Sun, Qingzhu; Wang, Yili; Li, Hongmin; Zhong, Nannan; Holmdahl, Rikard; et al.
Highlights: Low miR-144 was negatively correlated with elevated TLR2 which mainly expressed in hepatic Kupffer cells of NASH E3 rats. miR-144 directly targeted 3′UTR of rat TLR2 mRNA. miR-144 negatively regulated TLR2, TNF-α, IFN-γ and activation of NF-κB in NR8383 and BMM cells. Low miR-144 might enhance TNF-α and IFN-γ by targeting TLR2 in NASH of HFD-MetS E3 rats. Abstract: Objective: To analyze regulatory microRNA(s) leading to increased TLR2 expression in livers of high-fat-diet induced metabolic syndrome (HFD-MetS) in rats with non-alcoholic steatohepatitis (NASH). Methods: TLRs, inflammatory cytokines, candidate miRNAs targeting key TLR and its cellular localization were determined in liver. The miR-144 targeting TLR2 and regulating TLR2 signaling were further determined by dual luciferase reporter assay and miR-144 mimics or inhibitor. Results: Expression of miR-144 was negatively correlated with TLR2 expression in Kupffer cells. The miR-144 bound to 3′UTR of rat TLR2 mRNA. In addition, compared to control group, TLR2, TNF-α, IFN-γ and activation of NF-κB decreased after miR-144 mimic challenge in NR8383 cells and BMM from E3 rats, which could be compensated by Pam3CSK4; while opposite effects on their expressions were observed after miR-144 inhibitor administration, augmented by Pam3CSK4. Conclusion: Decreased miR-144 could enhance TNF-α and IFN-γ production by targeting TLR2 in vitro, and might contribute to TLR2 up-regulation and the progression of NASH in HFD-MetS E3 rats. This might offer a novel and potential target for NASH therapy.